Study on asexual propagation for Vietnamese ginseng species by tissue culture - Le Hung Linh; Khuat Thi Mai Luong; Nguyen Hoang Minh Khang; Dinh Van Phe; Trinh Hong Kien (International Journal of Medical Toxicology and Legal Medicine, 2024)
Plant tissue culture has been widely employed to maintain and conservemany important medicinal and endangered plant species. In this study, samples of four Vietnamese ginseng belonging to the Panax genus includingNgoc Linh, Lai Chau, Vu Diep and Tam That Hoang species were propagated by tissue culture technologies. MS medium supplemented with 05 mg/L 2.4-D was suitable for callus induction from rhizome tissue while MS supplemented with 1mg/L 2.4-D, and was suitable for callus induction from tuber tissue. The highest embryogenesis rate was exhibited on a medium containing MS + 1.0mg/L 2.4-D + 1mg/L NAA + 0.5mg/L TDZ for Ngoc Linh ginseng, Lai Chau ginseng and Vu Diep ginseng, while Tam That Hoang required to decrease the concentration of TDZ to 0.3mg/L, respectively. The optimum media for embryos that germinated into plantlets was MS + 0.5 mg/L NAA + 1.0 mg/L BA. The best rooting occurred in medium SH1/2 + 1.0 mg/L NAA + 0.2 mg/L BA + 0.2 g/L activated charcoal. In order to increase the survival rate of in vitro plantlets in the nursery, this research investigated the effect of substrate on the growth of ginseng plants propagated by tissue culture. In substrate composition, humus in mountain soils, perlite, vermiculite, and peat moss were used in different conditions (net house and natural condition).Our results demonstrated that treatment T3 (mixture of humus in mountain soils, perlite, and veclite at 2:1:3 was more favorable to the survival of ginseng seedlings after transplantation and the survival rate of the seedlings transplanted for 6 months was the highest (82.74%).Therefore, this study completed the propagation process starting from callus induction to plantlet regenerationfor tissue culture seedings of Vietnamese ginseng.